2018
DOI: 10.4049/jimmunol.1701641
|View full text |Cite
|
Sign up to set email alerts
|

FHR5 Binds to Laminins, Uses Separate C3b and Surface-Binding Sites, and Activates Complement on Malondialdehyde-Acetaldehyde Surfaces

Abstract: Factor H related-protein 5 (CFHR5) is a surface-acting complement activator and variations in the CFHR5 gene are linked to CFHR glomerulonephritis. In this study, we show that FHR5 binds to laminin-521, the major constituent of the glomerular basement membrane, and to mesangial laminin-211. Furthermore, we identify malondialdehyde-acetaldehyde (MAA) epitopes, which are exposed on the surface of human necrotic cells (), as new FHR5 ligands. Using a set of novel deletion fragments, we show that FHR5 binds to lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 55 publications
4
40
0
Order By: Relevance
“…It has been shown that MDA-epitopes mediate the clearance of damaged structures, such as oxidized low-density lipoproteins and dead cells (2). Various components of the innate immune system (e.g., scavenger receptors, natural immunoglobulin M (IgM) antibodies, CFH, and FHL-1) either directly or indirectly facilitate this process (14,(19)(20)(21). On the other hand, an impaired removal of MDA-carrying metabolic waste will promote inflammation (14,19,22).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that MDA-epitopes mediate the clearance of damaged structures, such as oxidized low-density lipoproteins and dead cells (2). Various components of the innate immune system (e.g., scavenger receptors, natural immunoglobulin M (IgM) antibodies, CFH, and FHL-1) either directly or indirectly facilitate this process (14,(19)(20)(21). On the other hand, an impaired removal of MDA-carrying metabolic waste will promote inflammation (14,19,22).…”
Section: Significancementioning
confidence: 99%
“…One of the major carriers of MDA-epitopes in vivo are apoptotic and necrotic cells (20,35). CFH as well as FHR5 have been found to bind to MDA-epitopes on necrotic cells (14,21). Therefore, we also tested the binding of recombinant FHR1 and FHR3 to necrotic human umbilical vein endothelial cells (HUVECs) by fluorescence microscopy.…”
Section: A Gwas Reveals a Cluster Of Genetic Variants Within Cfhr Genmentioning
confidence: 99%
“…The CFHR5 protein is a surface -acting complement activator and variations in the CFHR5 gene are linked to CFHR glomerulonephritis. 11 The CFHR5 protein binds to laminin -521, the major constituent of the glomerular basement membrane, and to mesangial laminin -211, fostering complement activation at damaged sites. 11 It is thus conceivable that a pathogenic variant of this protein could potentiate complement activation in an endothelial cell initially damaged by an immune complex process, leading to the subsequent development of complement -mediated TMA.…”
Section: Discussionmentioning
confidence: 99%
“…Factor H-related protein 1 can also bind to host surfaces via its FH-homologous C-terminus ( 22 , 29 ), and FHR-3 binds heparin through CCP2, which is homologous to CCP7 of FH ( 23 , 87 ). In addition, FHR-5 has a heparin-binding site in CCPs 5–7 ( 24 , 94 ). The functional relevance of these interactions needs to be investigated further, but they could anchor these proteins on certain cells and surfaces.…”
Section: Ligands Of Fh and The Fhr Proteins And Their Relevancementioning
confidence: 99%
“…As noted above, differences in ECMs and in domain composition of the FH family proteins may target FH and FHRs toward distinct sites, such as FH to the glomerular basement membrane ( via CCPs 19–20) and FHL-1 to the Bruch’s membrane ( via CCP7) ( 95 ). FHR-5 was shown to bind to MaxGel, an ECM extract, and de-regulate complement on this surface ( 32 ); a recent study identified laminin as an ECM ligand of FHR-5 ( 94 ).…”
Section: Ligands Of Fh and The Fhr Proteins And Their Relevancementioning
confidence: 99%